Correlates of flood preparedness in urban households: Evidence from the Greater Accra Metropolitan Area of Ghana - Daniel Kwabena Twerefou; Ernest Adu Owusu; Delali Benjamin K. Dovie (Environmental Challenges, 2023)
The annual floods in cities in Sub-Saharan Africa are exacerbated by the impacts of climate change. For coastal cities double flood burden from storms and sea level rise are phenomenal and in response, data is gradually emerging on the exposure of urban areas and households’ adaptation of which population determinants are mostly omitted. This paper uses a household survey of flood experiences, analyzed with the Tobit model to understand the social and demographic factors that drive households' preparedness for floods in the Greater Accra Metropolitan Area in Ghana. Findings show that the age and income of the household head and planned adaptation significantly increased the likelihood of households’ preparedness for floods. While community access to financial assistance reduced the likelihood of household preparedness, membership in social support groups and the availability of community-level social amenities and shelters increased the likelihood of household preparedness by 0.81 units (p<0.05), 1.72 units (p<0.01) and 1.33 units (p<0.01) respectively. Therefore, enhanced education and awareness of flood risks are major factors of flood disaster risk reduction amidst neighborhood networks towards scaling the relevance of anticipatory flood contingency planning in coastal urban planning and management and a recipe for mainstreaming the Sendai Framework for Disaster Risk Reduction.